Empowerment of "Winangsari" Coffee Farmer Group by the Agricultural Extension Center of Bawang District Pemalang Regency - bustomi, ahmad (Journal of Applied Transintegration Paradigm, 2022)
Abstract This research explain about the steps or process and impact of empowerment coffee farmer group â€œWinangsariâ€ by Balai Penyuluhan Pertanian Kecamatan Bawang. This research is qualitative descrivtive research. The aim of this research is to describe the process and impact of empowerment by Balai Penyuluhan Pertanian to coffee farmer group â€œWinangsariâ€. Data collecting technique utilizes interview, observation and documentation. Data validity utilizes triangulation of source and analized by data reduction, data display and conclution. The result of this research emerges the process of empowerment in the beginning is identification of potention and problemâ€, and then socialization step and the last is preparing of legality program. Afterwards, there are three main implementation of empowerment such as institution legality program, sertification of organic agriculture, and guiding program. The impact of empowerment are increasing price of coffe in Dusun Karangsari, getting business partner and trust from consument, ability to produce the coffee and opened of farmer thought to select in plant the coffee. Key Words: Empowerment, Balai Penyuluhan Pertanian, Farmer group. Abstrak Penelitian ini membahas mengenai apa saja tahapan atau proses serta dampak dari pemberdayaan Kelompok Petani kopi â€œWinangsariâ€ oleh Balai Penyuluhan Pertanian Kecamatan Bawang. Penelitian ini termasuk jenis penelitian deskriptif kualitatif. Tujuan dari penelitian adalah untuk mendeskripsikan proses serta dampak pemberdayaan oleh Balai Penyuluhan Pertanian kepada Kelompok Petani Kopi â€œWinangsariâ€. Teknik pengumpulan data dengan wawancara, observasi dan dokumentasi. Pengujian data dengan teknik triangulasi sumber kemudian dianalisis dengan proses reduksi data, penyajian data, dan penarikan kesimpulan. Hasil dari penelitian ini menunjukkan bahwa proses pemberdayaan tersebut diawali dengan tahap identifikasi potensi dan masalah, kemudian tahap sosialisasi dan persiapan program sertifikasi. Lalu ada 3 implementasi utama dari pemberdayaan kelompok tani yaitu program legalitas kelembagaan, sertifikasi pertanian organik dan program pendamping. Dampak pemberdayaan yakni meningkatnya nilai ekonomi kopi robusta di Dusun Karangsari, mendapatkan mitra dan kepercayaan dari konsumen, skill mengolah kopi yang meningkat dan terbukanya pikiran para petani untuk tidak sembarangan menanam dan membudidayakan tanaman. Kata Kunci: Pemberdayaan, Balai Penyuluhan Pertanian, Kelompok Tani.